Modelling And Simulation Of Air Classifier Cement Manufacturing - Ishak, Ku Esyra Hani Binti (2014)
The cement finish grinding circuit in cement manufacturing consumed the most electrical power in the cement industry. The total power consumption, however depends on the fineness of the grind, the particle size distribution and also the efficiency of the separation process of the ground particles. Improving the efficiency of the grinding and separation of the particles can give an improvement in the energy saving and cost reduction. The separation of particles is usually done by air classifier in a closed circuit. This thesis presents the development of a mathematical model that can describe the behavior of air classifier in the cement finish grinding circuit. Efficiency curves were used to model the high efficiency air classifier. The modelling work involves the taking of data in the full-scale plant. Industrial surveys were done to obtain data at the air classifier feed, air classifier reject and air classifier product. These data are important information in understanding how the air classifier behaves and helped in the development of the air classifier model. First, a review of mathematical modelling of air classifier is presented. Then, the results of the particle size distribution of from the testing are discussed. The efficiency curve was also developed. The simulator used is mainly based on the Whiten function to model the air classifier and predicts the reject and product output streams particle size distributions. The modelling of air classifier can be modelled in terms of dsoe, bypass, the fish hook and the sharpness of the curve.